AESTHETIC EVALUATION OF THE LOWER THIRD OF THE FACE COMPARING CEPHALOMETRIC AND PHOTOGRAPHIC ANALYSIS CONSIDERING NASOLABIAL AND LABIOMENTAL ANGLES IN YOUNG ADULT PAKISTANI POPULATION - Ahmad, Nofil; Mirza, Khalid Saeed; Ijaz, Faiza; Rabia Mushtaq; Zuhaa Mushtaq; Amna Khalid; Husnain Abbas (Journal of Ayub Medical College Abbottabad, 2021)
Background: Although the results derived from orthodontic treatment are focused at attaining an aesthetically pleasing soft tissue profile as directed by Angle’s paradigm, however hard tissue including bone and tooth dimensions also play a pivotal role in attaining the set goal. This study was focused on evaluating the comparison of photographs and cephalometric radiographic images to dictate the differences that might occur when the same aesthetic evaluation technique is applied. A cross sectional comparative study was carried out at Frontier college of dentistry, Abbottabad and Sharif Medical and Dental College, Lahore from June to November 2020. Methods: In this cross-sectional study, 60 subjects were incorporated as part of the study amongst which lateral cephalometric radiographic images and photographs, other diagnostic records such as dental casts were procured. The same analysis was applied to assess the lower third of the face in both the photographs and the radiographs with focus on the Labiomental and nasolabial angles for comparison. Results: The normal value of Nasolabial angle 102.10°±3.126° (NLA2) indicates the relationship of nose and upper lip which is within the normal range for the age group selected. No significant difference was found between the nasolabial angles measured by two separate methods (p-value is 0.67). Mean labiomental angle was found to be 120.70°±6.46°(LNA1) and 121.60°±5.386 degrees °(LMA2) respectively, which was within the normal range for the age group selected. Conclusion: There is no significant difference in the assessment of lower facial height and aesthetics between lateral cephalometric radiographic images and photographs taken from the camera.